Microbiota and lifestyle interactions through the lifespan. (November 2016) - Rampelli, Simone; Candela, Marco; Turroni, Silvia; Biagi, Elena; Pflueger, Maren; Wolters, Maike; Ahrens, Wolfgang; Brigidi, Patrizia
Abstract: Background: The human intestinal microbiota is an adaptive entity, being capable of adjusting its phylogenetic and functional profile in response to changes in diet, lifestyle and environment. Providing the host with functions important to regulate energetic homeostasis and immunological function, the gut microbiota is strategic to keep metabolic and immunological homeostasis during the entire lifespan. Scope and approach: In the present work we review studies exploring human gut microbiota variations at different age, describing the trajectory of ecosystem changes during the course of our life, from infancy to the old age. Gut microbiota variation mirroring subsistence strategy is also explored, with a particular focus on how the gut microbiota changes in response to modifications in the diet. Finally, we illustrate how an abnormal dietary intake could force microbiota to an obese-associated configuration, which concurs in compromising the host metabolic homeostasis. Key findings and conclusions: Our work allows appreciating the importance of the physiological flexibility conferred by the microbiota for modulating our metabolic and immunological phenotype along the course of our life. Further, the key role of the gut microbiota in providing an extra means of adaptive potential during our evolutionary history is highlighted, suggesting the importance of the intestinal microbiota-host interplay for the maintenance of human health and homeostasis in changing environments. On the other hand, different lifestyle and dietary factors, such as sanitization and antibiotic usage or high-fat diet, can force maladaptive changes in the microbiota configuration which could have negative effects on human health. Thus, it is important to modulate diet and lifestyle habits to keep a mutualistic gut microbiota layout along the course of our life. Highlights: The gut microbiota is an adaptive entity that coevolves with the human host. Diet, environment and hygiene practices affect the microbiota. Westernization-diseases, such as obesity, are associated to lifestyle determinants.